One Station / Dixon Jimoni.. [et al.] - Jimoni, Dixon; Matius, Asney; Saimon, Lerry; Rimin, Zulizah; Syadan, Mohd Hanif; Mohammad Jerry, Mohd Shah Rizan (2015)
The name of our company is ONE STATION. ONE STATION is a business that provides product to the customer in terms of beverages. We are making smoothie based on watermelon fruits with variety of fillings. The nature of our business is partnership. Our main office is located at One Borneo Hypermall. We expect to start up our business on January 2016. The future prospects of our business are people around Malaysia. In order to achieve our aim in this business, we plan to provide a product with a good quality to attract more customers in several years to go. We also would like to provide more products in a future. Other than that, we want to expand our marketing focus in the business by setting up more branches in other locations.